Don’t Let Them Eat Horse: Review of Kari Weil, Precarious Partners: Horses and Their Humans in Nineteenth-Century France - Gundermann, Christian (Humanimalia, 2024)
Review of: Kari Weil, Precarious Partners: Horses and Their Humans in Nineteenth-Century France. Animal Lives. Chicago: University of Chicago Press, 2020. xiv + 217 pp. 32 illus., 4 in colour. 97.00 (hb), 32.00 (pb).